f(c(

g(c(s(

R

↳Removing Redundant Rules

Removing the following rules from

f(c(X, s(Y))) -> f(c(s(X),Y))

where the Polynomial interpretation:

was used.

_{ }^{ }POL(c(x)_{1}, x_{2})= x _{1}+ 2·x_{2}_{ }^{ }_{ }^{ }POL(g(x)_{1})= 2·x _{1}_{ }^{ }_{ }^{ }POL(s(x)_{1})= 1 + x _{1}_{ }^{ }_{ }^{ }POL(f(x)_{1})= x _{1}_{ }^{ }

Not all Rules of

R

↳RRRPolo

→TRS2

↳Removing Redundant Rules

Removing the following rules from

g(c(s(X),Y)) -> f(c(X, s(Y)))

where the Polynomial interpretation:

was used.

_{ }^{ }POL(c(x)_{1}, x_{2})= x _{1}+ x_{2}_{ }^{ }_{ }^{ }POL(g(x)_{1})= 1 + x _{1}_{ }^{ }_{ }^{ }POL(s(x)_{1})= x _{1}_{ }^{ }_{ }^{ }POL(f(x)_{1})= x _{1}_{ }^{ }

All Rules of

R

↳RRRPolo

→TRS2

↳RRRPolo

→TRS3

↳Dependency Pair Analysis

Duration:

0:00 minutes